London Life and Labor - Carpenter, Niles (Quarterly Journal of Economics, 1932)
Journal Article London Life and Labor Niles Carpenter Niles Carpenter University of Buffalo Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 47, Issue 1, November 1932, Pages 150–159, https://doi.org/10.2307/1885191 Published: 01 November 1932